Volumetric Measurement of the Tensor Veli Palatini in Children: A Preliminary Normative Study - Gillespie, Julia Elizabeth (My University, 2024)
Background: The tensor veli palatini (TVP) is the primary muscle responsible for the dilation of the eustachian tube (ET). The TVP originates from the lateral wall of the ET and wraps around the pterygoid hamulus. The ET, when dilated, allows for equalization of air pressure between the atmosphere and middle ear. Literature suggests a clear relationship between middle ear pathologies, specifically otitis media with effusion (OME), and dysfunction of the TVP. While OME is extremely common in children, about 90% of children with a history of cleft palate have reported OME due to ET dysfunction, a rate much higher than their same age peers. Because there is a clear correlation between OME in patients with a history of cleft palate and the functioning of the TVP, the need to understand the morphology of abnormal craniofacial anatomy populations is vital. Studies have found that individuals with syndromes related to craniofacial differences (i.e. 22q11 deletion syndrome) and adults who have a history of cleft palate have significant differences in TVP volume, length, and thickness in comparison to their healthy counterparts. Despite there being some literature on TVP morphology in abnormal craniofacial populations, more literature is needed to describe the TVP morphology in those with typical anatomy, specifically in child populations. Objective: The purpose of this study is to investigate tensor veli palatini muscle volume in children without a history of cleft palate in order to better define normative values. Participants: There was a total of 11 healthy eight-year-old participants, 6 females and 5 males. Methods: Analysis of the TVP was completed using 3D MRI images and Amira Visualization Software. TVP volume was measured and compared between females and males. Results: The Mann-Whitney U test revealed that there were no significant TVP volume differences (U < .05, P = .273) between males (median = 673.906 mm3) when compared to females (656.022 mm3). The mean for the TVP volume of the entire sample was 648.51 ± 45.54 mm3. Conclusion: This study contributes preliminary insights into normative volumetric data for the tensor veli palatini muscle in a child population. No sexual dimorphism differences were noted for this study; however, studies with similar methodologies should be conducted with larger sample sizes and an increased age range as puberty may impact the morphology of this muscle. Results from this study will contribute to future understanding and comparison of cleft palate TVP volume. This will increase understanding of anatomic differences that have a role in middle ear pathologies, audiological ability, language development, and surgical planning processes for the cleft population.
Keywords: anatomy, normative, volumetric